Quantifying the expression levels of mexA and mexB genes in response to the efflux pump inhibitor PAβN in ciprofloxacin-resistant Pseudomonas aeruginosa isolated from urinary tract infections - Salwa A. Abdul Hussein; Abdulameer M. Ghareeb (Український Журнал Нефрології та Діалізу)
Urinary tract infections (UTIs) are among the most prevalent bacterial infections worldwide, occurring in both community and healthcare settings. Pseudomonas aeruginosa, a Gram-negative opportunistic pathogen, is one of the five most significant nosocomial bacteria and a major contributor to UTIs. This study aimed to quantify the expression levels of efflux pump genes mexA and mexB in response to the efflux pump inhibitor phenylalanine-arginine β-naphthylamide (PAβN) in ciprofloxacin-resistant P. aeruginosa isolates.